CARACTERIZAÇÃO DA FAUNA EDÁFICA EM PLANTIOS DE Eucalyptus spp. - Juliana Garlet; Ervandil Correa Costa; Jardel Boscardin (Ciência Florestal, 2013)
Forest soils provide good conditions for the development and the establishment of soil fauna, manly by the deposition of litter. However, monoculture systems conducted in a single food providing substrate, can promote the development of certain fauna groups over others, causing outbreaks of pest species. The aim of this study was to characterize the soil fauna and its relationship with meteorological variables, in plantations of Eucalyptus spp. This study was conducted in six stands of three species of Eucalyptus: Eucalyptus dunni Maiden, Eucalyptus grandis Maiden and Eucalyptus grandis x Eucalyptus urophylla S. T. Blake (clone hybrid) and two ages (planted in 2006 and 2007). The stands was located at Cabanha da Prata and Chica Barbosa farms in Alegrete, and at Taquari farm in São Francisco de Assis, Rio Grande do Sul state. For sampling soil insects, pitfall traps were used. Eight traps were installed ten meters apart from each other, distributed in two rows in the center of each stand, totaling 48 traps. Samples were collected fortnightly from September 2008 to August 2009. After counting and identifying the taxonomic groups, the parameters of richness (total number of taxonomic groups), abundance and shannon diversity index were determined. The results were analyzed using 3x2 factorial model (three species and two ages) in a randomized design with Test F. During this study, 8.811 specimens representing 12 taxonomic groups were collected. The groups Coleoptera, Hymenoptera, and Diptera had the highest percentages of individuals collected: 31.1, 23.2, and 19.6%, respectively. The plantation with three years of age had a higher number of individuals compared to the stands of two years of age. The species Eucalyptus grandis and Eucalyptus grandis x Eucalyptus urophylla had a higher number of individuals collected when compared with the species Eucalyptus dunnii at both ages. Thus, the species and age of the planting exerted influence on the organisms collected.